The nurse coordinator role: fulfillment of the nursing profession's compact with society - Anne H. Gross; Jessica Driscoll; Laura Ma (BMC, 2019)
Abstract The implementation of a new role in healthcare teams frequently emanates from emerging or changing needs in the care delivery system or expressed needs of clinicians, patients or caregivers. In this commentary on the experience of the nurse coordinator role in Israel we suggest based on similar experiences in the United States, that effective implementation is accomplished when the functions of the role are well delineated with respect to other members of the team and informed by the needs of patients, their caregivers and clinicians. The outcomes expected from those performing the role should be established and measured over time.